2009
DOI: 10.2478/v10078-009-0020-7
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Airway Resistance indices and Maximal Oxygen Uptake in Young Adults

Abstract: Relationship Between Airway Resistance indices and Maximal Oxygen Uptake in Young Adults The present study aims at assessing the relationship between airway resistance indexes (FEV1, FVC and FEV1/FVC) and maximal oxygen uptake (Vo2max) in young adults. Subjects of the study included 50 healthy males (age, 22.1 ± 2.47 years; FEV1, 3.41 ± .66 liter; FVC, 3.96 ± .56 liter; VO2max, 38.83 ± 9.83 ml.kg-1.min-1) studying at Shahid Chamran University of Ahvaz. After determining subjects' volumes of FEV1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
13
2
Order By: Relevance
“…The result of this study shows that between amounts of FVC with peak oxygen consumption has a positive significant correlation. The findings from the present study are consistent Fatemi et al [3] and Rabiee et al [17]and inconsistent Haji Nia et al [8] with those reported in the literature.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The result of this study shows that between amounts of FVC with peak oxygen consumption has a positive significant correlation. The findings from the present study are consistent Fatemi et al [3] and Rabiee et al [17]and inconsistent Haji Nia et al [8] with those reported in the literature.…”
Section: Discussionsupporting
confidence: 82%
“…Fatemi et al [3] reported that a significant correlation among the three independent variables of FEV1, FVC, FEV1/FVC and projected VO2max values in 50 healthy males with range of age, 22.1 ± 2.47 years. Rabiee et al [17] investigated the Relationship between body composition and maximum oxygen consumption with pulmonary function in 20 subjects show that there was a significant positive correlation between Cardio respiratory fitness and respiratory parameters in light weight in the FEV1 and FVC and heavy weight groups in the FEV1 and FVC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Mehrotra et al, 1998;Mazica et al, 2015;Adegoke & Arogundade, 2002;Bilgin, Çetin, & Pulur, 2010 ). Some studies have suggested the significant positive relationship between aerobic capacity and pulmonary function tests (Harries, 1994;Bilgin et al, 2010;Fatemi & Ghanbarzadeh, 2010;Chaitra, Pandurang, Nagaraja, & Vijay, 2011). The significant improvement in the pulmonary functions have been found in endurance trained athletes: swimmers (Mehrotra et all., 1998;Nilesh et al, 2012), basketball and water polo players, rowers (Mazica et all., 2015), cyclists, middle and long distance runners (Harries, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Many authors have proved the correlation between the possibilities of the respiratory system and aerobic capacities of the sportsmen (Bilgin et al, 2010;Fatemi & Ghanbarzadeh, 2010;Chaitra, Pandurang, Nagaraja, & Vijay, 2011;Harries, 1994). Many observations have shown that in some sports the result is to the great extent determined by aerobic capacities of the sportsmen.…”
Section: Introductionmentioning
confidence: 99%